1998
DOI: 10.1177/095632029800900407
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxyphthaloyl β-Lactoglobulin. IV. Antiviral Activity in the Mouse Model of Genital Herpesvirus Infection

Abstract: The spread of sexually transmitted infections caused by herpes simplex virus type 2 (HSV-2) has continued unabated despite educational efforts generated in response to the human immunodeficiency virus (HIV) epidemic. Given the absence of effective vaccines, this indicates the need to develop prophylactic measures such as topical antiviral agents. Chemical modification of bovine β-lactoglobulin (β-LG), the major protein of whey, by hydroxyphthalic anhydride (3HP) led to the generation of a potent HIV-1 inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…As summarized in Tables 1 and 2, the vaginal HSV-2 model used in these experiments is reproducible, with an incidence of infection in untreated animals virtually identical to that reported before (Kokuba et al, 1998). Thus, virus was first isolated from untreated mice infected with 2×10 5 p.f.u of HSV-2 at 3 days post-infection (p.i).…”
Section: Resultsmentioning
confidence: 94%
“…As summarized in Tables 1 and 2, the vaginal HSV-2 model used in these experiments is reproducible, with an incidence of infection in untreated animals virtually identical to that reported before (Kokuba et al, 1998). Thus, virus was first isolated from untreated mice infected with 2×10 5 p.f.u of HSV-2 at 3 days post-infection (p.i).…”
Section: Resultsmentioning
confidence: 94%
“…However, the modified peptides showed a cytotoxic effect on the Vero cells. Kokuba, Aurelian, and Neurath (1998) reported that 3-HP-b-Lg prevented HSV-2 infection in the mouse model of genital HSV-2 infection, suggesting that 3-HP-b-Lg might be an efficacious agent for preventing vaginal transmission of genital herpesvirus infections. Schoen, Corver, Meijer, Wilschut, and Swart (1997) also reported that acylated milk proteins were effective against influenza virus.…”
Section: Effect Of Chemical Modifications On the Antiviral Activity Omentioning
confidence: 97%
“…Our group previously discovered a series of chemically modified bovine milk proteins with anti-HIV-1 activity (46). One of the most efficient antiviral agents is 3-hydroxyphthalic anhydride-modified ß-lactoglobulin (3HP-ß-LG), which is a promising candidate microbicide to prevent the sexual transmission of HIV-1 because of its broad antiviral activity against HIV-1, HIV-2, SIV, and HSV and against Chlamydia trachomatis (25,28,33,47,49,51). Most importantly, 3HP-ß-LG is highly soluble and stable for long-term storage.…”
Section: Discussionmentioning
confidence: 99%